Evaluation of thermo-mechanical properties of graphene/carbon-nanotubes modified asphalt with molecular simulation. Issue 4 (4th March 2017) - Zhou, Xinxing; Zhang, Xiao; Xu, Song; Wu, Shaopeng; Liu, Quantao; Fan, Zepeng
Abstract: A comparative study was conducted to determine the effects of graphene and carbon nanotubes on the thermo-mechanical properties of asphalt binder using molecular simulations and experiments. Micro-morphology of graphene and carbon nanotubes was measured by scanning electron microscopy. Thermal stability and glass transition temperature were investigated by differential scanning calorimeter. Simulation results indicated that the T g had slightly changed for graphene-modified asphalt (GMA) and carbon nanotubes-modified asphalt (CNsMA) and that the thermal expansion coefficients and thermal conductivity increased along with the adding amount of graphene or carbon nanotubes. The T g calculated by density–temperature method was closer than the experimental T g and the T g decreased in the order of CNsMA, GMA and asphalt. Young's modulus of asphalt, GMA and CNsMA were 9.2658, 25.7563 and 17.8249 GPa at 298 K, respectively, which indicated that thermo-mechanical properties of asphalt showed considerable improvements after the addition of graphene or carbon nanotubes, and carbon nanotubes-modified asphalt and GMA were promising candidates for the future modified asphalt.